Central odontogenic fibroma with giant cell granuloma-like features: a case report and comprehensive literature review - de Carvalho Kimura, Talita; Sari Precetti, Renata; Kaline Farias Bezerra, Hélen; Roger Santos Silva, Alan; Carolina Prado Ribeiro, Ana; Agustin Vargas, Pablo (Journal of Oral Diagnosis, 2024)
Central odontogenic fibroma (COF) is a rare benign tumor from odontogenic mesenchyme, accounting for less than 5% of odontogenic tumors. Central giant cell granuloma (CGCG) is also benign but locally aggressive, featuring multinucleated giant cells in a fibrovascular stroma. Hybrid lesions with features of both COF and CGCG are extremely rare, with fewer than 50 cases reported. This paper presents a case of a hybrid COF-CGCG lesion in a 33-year-old female with an asymptomatic, well-defined unilocular radiolucent lesion between mandibular premolars, causing root resorption and tooth displacement. Histopathological analysis revealed a mixture of inactive odontogenic epithelium and multinucleated giant cells embedded in a dense, collagenized stroma. The patient showed no signs of recurrence after six months of follow-up. This case highlights the rarity and diagnostic challenges of COF-CGCG hybrid lesions, emphasizing the need for further research to understand its pathogenesis and guide management.